Acoustofluidic Patterning inside Capillary Tubes Using Standing Surface Acoustic Waves. (15th January 2022) - Maramizonouz, Sadaf; Jia, Changfeng; Rahmati, Mohammad; Zheng, Tengfei; Liu, Qiang; Torun, Hamdi; Wu, Qiang; Fu, YongQing
Highlights: Capillary tubes & SAW devices used to pattern particles in no-flow & flowing setups Rectangular tube: particle lines are parallel to tube sidewalls for all directions Circular tube: particle alignment depends on their position along the tube height Bottom/mid height: particles lines parallel/perpendicular to the tube direction Continues flow: particles always pattern in lines parallel to the flow direction Abstract: Acoustofluidic platforms have great potentials to integrate capillary tubes for controlling and manipulating microparticles and biological cells in both non-flowing and continuous-flow settings. In order to effectively manipulate microparticles/cells inside capillary tubes, it is essential to fully understand and control the patterns generated inside the capillary tubes with different cross-sections, and to investigate the influences of configuration and position arrangement of electrodes along with the capillary tubes. This paper aims to systematically investigate the patterning and alignment of microparticles inside glass capillary tubes using thin film surface acoustic wave (SAW) devices. Through both experimental studies and numerical modelling, effects of various cross-section geometries of the capillary tubes and their positioning with respect to the direction of interdigital transducers (IDTs) of the SAW device in both a stationary fluid and a continuous flow fluid were studied. Results showed that for the rectangular glass capillary tubes, the patterned lines of particles are parallel to the tube's side walls, irrelevant to the tube positions along with the IDTs, which is mainly caused by the standing wave field generated inside the rectangular glass tube. Whereas for the circular glass capillary tubes, alignment patterns of particles are quite different along the tube's height. At the bottom of the circular tube, particles are patterned into lines parallel to the tube direction, because the acoustic waves propagate into the water and form a standing wave along the direction of the circular tube. Whereas at the middle height of the tube, the particles are patterned into lines perpendicular to the tube direction, because the formed standing waves also propagate around the circular cross-section of the tube and are perpendicular to the tube direction. For the cases with a continuous liquid flow, under the agitation of acoustic waves, particles are patterned in lines parallel to the flow directions for both the rectangular and circular glass tubes, and the fluid flow enhances and smoothens the patterned lines of the particles. Graphical Abstract: Image, graphical abstract